Le strutture con tipo: uno studio di alcune configurazioni dell'italiano parlato. - Marano, Luca (Italianist, 2013)
The aim of this article is to deal with structural and functional issues regarding the expression TIPO, in constructions such as ci vediamo tipo alle cinque. This paper argues that this element is not simply a filler, but is linked to particular focus issues. After a review of the previous accounts of TIPO, particularly in dictionaries and semantic studies, the article concentrates on formal, functional, and pragmatic issues concerning TIPO structures. This element seems to have interesting functions when put in specific environments. The sample of the study is made up of middle-class young people aged eighteen to twenty-five. TIPO rarely appears in written texts, so it seems to be a typical element of spoken texts of Italian native speakers.